Pelatihan Praktek Hafalan Surah Pendek Dalam Kegiatan Festival Anak Sholeh Di Desa Lama Kecamatan Sei Lepan Kabupaten Langkat - Syahrul Kodrah; Rani Febriyanni; Syahrizal Amri; Novia Putri; Lily Aulia (peduli riset dan pengabdian masyarakat, 2023)
Community service (PKM) is one of the pillars of the Tri Dharma of Higher Education. One form of its realization is through cooperation between the regional government and universities in the form of implementing KKN which is sustainable and mutually beneficial. The purpose of this PKM is to improve children's competence, morals and manners, increase enthusiasm in learning Islamic religion, develop interests and talents and increase the creativity and self-confidence of children in the Old Village through the implementation of an activity program entitled